Publicidad en los medios de comunicación y su incidencia en el comportamiento cultural de los jóvenes de la ciudadela Carlos Alvarado, cantón Babahoyo año 2018 - Calvache Pulecio, Alicia Marilú (2018)
Advertising in the mass media is of great interest, but nevertheless, the advertising message adopts different characteristics depending on the medium in question, so the company or advertising agency must study carefully... This case study gave the opportunity to learn about advertising in the media and the influence on the behavior of young people in the “Carlos Alberto” sector of the Babahoyo canton, Province of Los Ríos. Knowing in turn the problem that has caused the effects of advertising in this sector. Within this case, the observation method, experimental and exploratory research were used, which contributed to the development of the variables and the hypotheses of the investigation. In addition to obtaining clear and precise data, for a broad criterion about advertising and its contents. Once the problem was known, I can search for and propose solutions based on satisfying the needs of the youth of the “Carlos Alvarado” sector, in addition to implementing a proposal that benefits them.